Impact of plant protein functionality and extrusion conditions on texture of high moisture meat analogs (HMMAs) - Plattner, Blake John (Kansas State University, 2022)
The current food landscape in North America is one in which consumers will pay more for premium, nutritious, and healthy products. Plant-based meat fits under this umbrella, and provides an alternative food option for consumers who do not prefer to eat animal meat, for animal welfare, environmental, or health reasons. Extrusion technology is the primary processing method for the development and production of plant-based meat, also called ‘meat analogs’. Textured vegetable protein (TVP)-based products have been predominately used in the past to make plant-based patties, meatballs, nuggets, and other product forms; but a new version of meat analogs has evolved recently with advances in extrusion technology. High moisture meat analogs, also known as HMMAs, are plant-based meat products designed to mimic the aesthetic and nutritional qualities of whole animal muscle meat cuts, like steak or fillets. The intent of this research was to study various plant protein sources, and also investigate the impact of extrusion equipment design and processing techniques on the overall texture and quality of HMMAs. In the first part of this study, five different plant protein recipes were processed on a Wenger TX-52 pilot-scale extruder equipped with a long downstream cooling die. Three recipes utilized only single-protein sources, namely soy (S), wheat (W), and pea (P). The other two recipes consisted of blends of soy proteins with wheat (WS) and pea-based (PS) protein sources. In-barrel moisture (IBM) and cooling water injection rate were optimized for each treatment to achieve optimum texturization. Clear differences were observed in rapid-visco analysis pasting profiles of the single-protein recipes, with higher peak viscosity for W (169 cP) and S (167 cP) as compared to P (102 cP). Cutting test on HMMA products using a TA-XT2 texture analyzer demonstrated much higher firmness (5,635 and 5,220 g, respectively) and toughness (36,725 and 37,370 g.sec, respectively) for W and P, as compared to the other three recipes that had soy proteins (firmness 2,020 – 2,680 g and toughness 11,905 – 16,815 g.sec), while textural profile analysis (TPA) data indicated that the S recipe had highest hardness (10,925 g) and chewiness (6,890) and lowest springiness (0.87) values. The overall conclusion was that soy protein led to the highest quality HMMA, also confirmed based on visual analysis, forming uniform and laminated or layered products. The overall textural quality and consistency of the wheat and pea-based HMMAs were inferior to soy. These products contained thick outer shells, possibly due to inadequate cooling in the die. The second part of this study focused on pea protein, given its labeling advantages and high demand. Four pea protein types were analyzed to assess differences in their raw material properties and then processed on a twin-screw extruder, using the same die set up as in the first study, to evaluate functionality differences. It was found that the pea protein types exhibiting lower solubility (PPI2 and PPI3), measured using the Biuret method and confirmed with rapid-visco analysis pasting data, led to increased product firmness (10,960-13,550 g) and better overall visual quality. Additionally, complementing pea protein isolate (PPI) with pea protein concentrate (PPC) was found to improve product quality and reduce outer shell formation. When compared to cooked animal meat anchors, using a TA-XT2 texture analyzer, HMMA products displayed similar hardness, firmness, and toughness to that of animal meat. The third and final part of this study was also conducted with pea proteins, with an emphasis placed on extrusion equipment design and processing parameters. Two recipes, varying only in PPI inclusion amount (50-60%), were processed on a Wenger TX-52 pilot-scale extruder with a thinner, longer cooling die (5/16” diameter) as compared to the previous experiments, at different extrusion process conditions. As feed rate increased from 25 to 35 kg/hr, hardness (21,005-31,230 g) and toughness (30,345-43,285 g.sec) values significantly increased for the HMMA products. Higher barrel temperatures (150°C versus 130°C) and PPI inclusion (60% versus 50%) also increased texturization, but not as significantly as feed rate. This research demonstrates the importance of understanding the impact of raw materials, extruder hardware, and processing conditions on final product properties and overall textural quality of HMMAs. Generally, pea proteins exhibit lower functionality compared to soy and wheat proteins, but with specialized recipes and a high-level understanding of extrusion processing parameters and cooling die design, high-quality HMMA products can be developed using peas.
Keywords: Plant-based meat; Pea protein; Extrusion; High moisture meat analog; Texturization; Protein cross-linking